Characterization of PbS films deposited by successive ionic layer adsorption and reaction (SILAR) for CdS/PbS solar cells application - C E Pérez-García; S Meraz-Dávila; G Arreola-Jardón; F de Moure-Flores; R Ramírez-Bon; Y V Vorobiev (Materials Research Express, 2020)
The properties of PbS thin films deposited by Successive Ionic Layer Adsorption and Reaction (SILAR) method were analyzed and applied in PbS/CdS heterojuction solar cells. In this study for n-type layer, cadmium sulfide thin films were deposited on transparent conductive oxide (ITO) substrates by Chemical Bath Deposition (CBD) technique followed by deposition of PbS film using different deposition cycles, 15, 20, 30, 40 and 60 to obtain different thicknesses from 90 nm to 658 nm. Morphological, structural and optical properties were investigated. The roughness of the PbS films were found to be in the range of 10–162 nm, depending on the number of cycles. The films of PbS present a band gap value of 0.6 eV. PbS/CdS heterojunctions were studied as solar cells, it was observed that 40 cycles PbS film has a greater photovoltaic conversion efficiency.